Revealing the fate of the phenylcoumaran linkage during lignin oxidation reactions. Issue 11 (2nd March 2018) - Lahive, Ciaran W.; Lancefield, Christopher S.; Codina, Anna; Kamer, Paul C. J.; Westwood, Nicholas J.
Abstract : Phenylcoumaran linkages are shown, for the first time, to be oxidised to phenylcoumarones in lignin during oxidations with DDQ. Abstract : The fate of most lignin linkages, other than the β-O-4, under selective oxidation conditions is largely unknown. In this work we use advanced β-5 lignin model compounds to identify the fate of phenylcoumaran units in a softwood lignin during oxidation with DDQ. By using model compounds combined with detailed characterisation of the oxidised lignin polymer using HSQC and HMBC NMR we show that phenylcoumarones are a major product, and therefore constitute a novel non-native β-5 linkage in oxidised lignins. Additionally, the reactivity of these units in lignin led us to further investigate their connectivity in lignin, showing that they are found as both phenolic and etherified units. The findings and approach developed here will help improve the efficiency of selective oxidative lignin depolymerisation processes, particularly those aimed at the upgrading of softwood lignin in which phenylcoumarans are a major linkage.